Formation energy of graphene oxide structures: A molecular dynamics study on distortion and thermal effects. (April 2015) - Fonseca, Alexandre F.; Zhang, Hengji; Cho, Kyeongjae
Abstract: Ab initio predictions for the stability of different graphene oxide (GO) structures have been shown to conflict with experimental observations. While ab initio studies predict that the most stable GOs are fully oxygen-covered (either with epoxide or hydroxyl), stable as-produced GOs are partially oxygen-covered and predominantly epoxide-covered structures. Although this discrepancy is being examined in terms of calculations of free energies of GOs and large diffusion energy-barriers for oxygen groups on graphene, there is still a lack of understanding on the energetic properties of GOs using classical molecular dynamics, which is able to investigate their structural distortion. Here, using the reactive empirical bond order (REBO) molecular dynamics potential, we compute the free energy and binding energy of GOs at different oxygen concentrations and epoxide to hydroxyl ratios, as well as the distortion energies of graphene lattice. Although epoxide causes more distortion on the carbon hexagonal planar structure, it provides more stability to the GO structure. The difference between free energy and binding energy of GOs is shown to be independent of oxygen coverage. These results allow gaining more insight on the issue of GO stability and show that REBO can capture most of experimental properties of GOs.